Fatwa Nahdlatul Ulama Tentang Suap Politik - Ahmad Muhajir (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
Islamic studies on money politics written in Indonesian rarely analyze the opinions of Islamic social organizations (ormas). Most of the previous researchers conducted their own search for the legal status of money politics, either by referring to the hadith about risywah (bribery) or using a certain Islamic perspective, for example, maqashid as-syari’ah. However, the personal opinions of these researchers, most of them are not very popular, are not as echoed in the public as fatwas issued by major Islamic organizations in Indonesia. In this article, I analyze the fatwa of Nahdlatul Ulama (NU) on the issue of money politics. Apart from being widely known by the Indonesian people and having tens of millions of members, NU has a distinctive fatwa on this issue that uses the concept of intention as a reference. This fatwa when analyzed in detail led to the conclusion that the prohibition of giving a gift to voters turned out to have an exception.